Flower baggings in affecting mangosteen fruit qualities at harvest and during storage. Issue 1 (May 2020) - Widodo, S E; Kamal, M; Zulferiyenni,; Chandra, D; Kusuma, D W
Abstract: Physiological causes and insect attact are believed to increase yellow latex exudates in mangosteen fruits. To inhibit the causes, flower bagging should be applied. This research was aimed at studying the effects of flower baggings to two different flower developments in affecting mangosteen fruit qualities at harvest and during storage. Three bagging materials (unbagged, paper, and baloon) were applied to flowers of 2 and 4 weeks after anthesis (WAA). The fruits were sampled every 2 weeks during the periods of 8-16 WAA. The results showed that except α-mangosteen content that was slightly decreased during the latest periode of fruit growth by bagging at preharvest, flower baggings of both bagging materials and application periods mostly did not affect mangosteen fruit qualities at harvest, but they affected fruit shelf-life and qualities during storage. Flower baggings resulted in increased fruit shelf-life, with paper bagging applied in 2 WAA was better than that applied in 4 WAA. Paper bagging in 2 WAA resulted in the mangosteen fruit shelf-life of 29 days compared to 4 WAA which resulted in 14 days shelf-life. This research proved also that the occurence of yellow latex was much more likely affected by physiological causes, not by insect attacts.